1998
DOI: 10.1107/s0108768197014547
|View full text |Cite
|
Sign up to set email alerts
|

Channel-Type Crystal Packing in the Very Rare Space Group P4212 with Z' = 3/4: Crystal Structure of the Complex γ-Cyclodextrin–Methanol–n-Hydrate

Abstract: The crystal structure of the title compound is discussed with focus on its unusual crystal packing mode. Thecyclodextrin molecules stack in columns which have internal channels and additional large channels are formed between the columns. Both types of channels are so wide that more or less free diffusion of water and small guest molecules is possible, preventing characterization of the solvent and guest arrangements. Although the space group P42 1 2 (no. 90) and the unit-cell content Z H = 3 4 are extremely r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 9 publications
2
35
0
Order By: Relevance
“…[18] Atom coordinates from both energy minimized quantum mechanical calculations and crystallographic data of a-CD, [26,27] b-CD, [28,29] and g-CD, [30,31] were used as input structures. An electron density cut-off value of 0.002 au, common in literature, [32][33][34] was chosen to define the surface of the molecule.…”
Section: Resultsmentioning
confidence: 99%
“…[18] Atom coordinates from both energy minimized quantum mechanical calculations and crystallographic data of a-CD, [26,27] b-CD, [28,29] and g-CD, [30,31] were used as input structures. An electron density cut-off value of 0.002 au, common in literature, [32][33][34] was chosen to define the surface of the molecule.…”
Section: Resultsmentioning
confidence: 99%
“…The tetragonal-columnar form of g-CD provides the internal channels for the CD cavity and additional channels form between the columns. 36 Both types of channels are assumed to be large enough to include two SA molecules for every g-CD molecules. Hence, for the specific 4:1 complex, two SA molecules each were concluded to be located in the cavity of g-CD and in the intermolecular spaces of g-CD columns.…”
Section: Molecular Arrangement Of Sa In 2:1 and 4:1 Complexesmentioning
confidence: 99%
“…Each trimer is made of crystallographically independent molecules assembled in a stacked vase-like cluster (Figure 2). The stacked trimer motif is not unknown for γ-CD molecules (see for example CSD refcodes FEJFIJ, FEJFOP, NUNRIX, SIBJAO, SIBJES) [17][18][19]; however the concept of vase-like packing has not been previously reported. It has also been reported that β-CD molecules crystallise as trimers (CSD refcodes RIPKIL, OCIGAK) [20,21] or tetramers [22,23].…”
Section: Resultsmentioning
confidence: 99%
“…A honeycomb or quasi-hexagonal pattern ensures effective close packing [19,26], and for CDs it was reported for the first time by Saenger in 1980, while describing the general arrangement of CDs in crystals, as "hexagonal packing of stacks" [5]. A careful analysis of the reported channel-type structures of α-CD inclusion complexes, including hydrates, in the CSD shows that honeycomb packing is observed in 27 out of 50 structures (CSD refcodes of these structures are reported in the Supplementary Information), though this particular structural feature has been rarely reported In the solid state α-CD molecules have always been known, to the best of our knowledge, to pack as either distinct entities or dimers [6,8].…”
Section: Resultsmentioning
confidence: 99%